Building a Data-Driven Multiple Daily Insulin Therapy Model Using Smart Insulin Pens. (May 2022) - Harbison, Rocio; Hecht, Michele; MacLeod, Janice
A growing suite of connected devices including Bluetooth or cellular-enabled glucose monitoring devices, smart insulin pens, pumps, fitness trackers, blood pressure, and heart rate and weight monitors present a golden opportunity to build a data-driven clinical practice model including remote monitoring capability and virtual care. This paper will discuss this approach using diabetes as a case study and smart insulin pens as a use case. As payment and practice approaches evolve, there is growing interest from both patients and their health care teams in virtual care made possible by remote monitoring capability. Here, we will define the category of smart insulin pens, describe the hallmarks of a data-driven practice model, and delineate the steps to take to incorporate remote monitoring capability with smart insulin pens into diabetes care for injection therapy patients.